Case Report: Effectiveness of Targeted Treatment in a Patient With Pancreatic Cancer Harboring PALB2 Germline Mutation and KRAS Somatic Mutation - Wu, Wei; Liu, Yu; Jin, Yuzhi; Liu, Lulu; Guo, Yixuan; Xu, Mian; Hao, Qing; Li, Dazhi; Fang, Weijia; Zhang, Aibin; Zhao, Peng (Frontiers in Medicine, 2022)
Pancreatic cancer is one of the most leading cause of cancer death worldwide. The rapid development of next-generation sequencing (NGS) and precision medicine promote us to seek potential targets for the treatment of pancreatic cancer. Here, we report a female pancreatic cancer patient who underwent radical surgical excision after neoadjuvant chemotherapy. After the surgery, the patient underwent gemcitabine + S-1 therapy, capecitabine + albumin paclitaxel therapy and irinotecan therapy successively, however, MRI review revealed tumor progression. Surgical tissue sample was subjected to next-generation sequencing (NGS), and PALB2 germline mutation and KRAS somatic mutation were identified. The patient then received olaparib (a PARP inhibitor) + irinotecan and the disease stabilized for one year. Due to the increased of CA19-9, treatment of the patient with combination of trametinib (a MEK inhibitor) and hydroxychloroquine resulted in a stable disease (SD) with a significant decrease of CA19-9. This case demonstrated that the NGS may be a reliable method for finding potential therapeutic targets for pancreatic cancer.